Asociación entre insomnio e inactividad física en estudiantes de Medicina en cuarentena por SARS-Cov-2 - Loyola García, Sthephannie Elízabeth (2021)
To evaluate if there is an association between insomnia and physical inactivity in medical students of the Universidad Nacional de Trujillo in SARS-Cov-2 quarantine. Material and Methods: Descriptive observational cross-sectional and correlational study that evaluated 4th, 5th, 6th and 7th year medical students of the National University of Trujillo in quarantine for SARS-Cov-2 during March 16 to June 30, 2020. Students diagnosed with insomnia, who suffer from any sleep disturbance other than insomnia, or who are under medical treatment for any chronic or acute illness, including insomnia, were excluded. Results: It was found that 46.75% of the students evaluated presented insomnia during quarantine for SARS-Cov-2, and 71.89% presented physical inactivity during quarantine for SARS-Cov-2. The association of both variables was evaluated using the Chi-square distribution, obtaining a X2 =13.96 with a p=0.0001, a 95% confidence interval (CI) of <1.55-4.25> was found. Conclusion: There is a significant association between insomnia and physical inactivity in medical students of the National University of Trujillo in SARS-Cov-2 quarantine.